Is Multifocality an Indicator of Aggressive Behavior in Small Bowel Neuroendocrine Tumors?. Issue 9 (October 2017) - Choi, Allen B.; Maxwell, Jessica E.; Keck, Kendall J.; Bellizzi, Andrew J.; Dillon, Joseph S.; O'Dorisio, Thomas M.; Howe, James R.
Abstract : Objectives: Many patients with small bowel neuroendocrine tumors (SBNETs) have multifocal tumors (MFTs), but the frequency of MFTs has varied widely across SBNET studies. It is also unclear whether patients with MFTs have more advanced disease or worse clinical course than do those with unifocal SBNETs. We set out to determine the frequency of multifocal and unifocal SBNETs and compare clinicopathologic factors, somatostatin receptor 2 expression, and survival. Methods: Clinicopathologic variables from 179 patients with surgically managed SBNETs were collected. Statistical comparisons were made using Welch t -test, Wilcoxon test, and Fisher's exact test. Survival was assessed using the Kaplan-Meier method. Somatostatin receptor 2 expression was analyzed by quantitative polymerase chain reaction, and Ki-67 expression by immunohistochemistry. Results: Multifocal tumors were found in 45% of patients with SBNETs. Clinicopathologic factors such as grade, TNM stage, presence of distant metastases, mean somatostatin receptor 2 expression, success of imaging modalities, and preoperative and postoperative hormone levels were not significantly different between multifocal and unifocal groups. Progression-free survival and overall survival were also not significantly affected by multifocality. Conclusions: Clinicopathologic features and survival of patients with MFTs and unifocal tumors are remarkably similar. Although the etiology of MFTs is unclear, patients with MFTs do not have a more aggressive clinical course than patients with unifocal SBNETs.